KERAGAMAN GENETIK KAYU KUKU (Pericopsis mooniana Thw) PROVENANS SULAWESI TENGGARA PADA TINGKAT SEMAI - Tri Pamungkas Yudohartono; Ari Fiani; Yuliah Yuliah (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2019)
High demand of kayu kuku (Pericopsis mooniana Thw) has threatened the existence of its populations in natural distribution. Therefore, ex-situ conservation need to be carried out to protect them from extinction. Preparation genetic materials in nursery stage is very important to support the success of establishing ex-situ conservation plot. The objective of this research is to observe the role of genetic factor in the growth characteristics of kayu kuku seedlings in which the seed was originally collected from South East Sulawesi provenance. This research was arranged in Completely Randomized Complete Bock Design with 40 families in three replications. The result showed that genetic difference among the tested families affected the growth characteristics of seedling for height, diameter and sturdiness index. Genotype and phenotype correlation between height and diameter traits were 0.95 and 0.74 respectively. It revealed that high genetic diversity of kayu kuku could be observed in seedling stage, and indicated an important of genetic materials collected from Southeast Sulawesi provenance for further conservation and tree improvement program.